Zircon ages and Hf isotopic constraints on sources of clastic metasediments of the Slyudyansky high-grade complex, southeastern Siberia: Implication for continental growth and evolution of the Central Asian Orogenic Belt - Kovach V.; Salnikova E.; Wang K.-L.; Jahn B.M.; Chiu H.-Y.; Reznitskiy L.; Kotov A.; Iizuka Y.; Chung S.-L. (My University, 2013)
We present results of combined in situ U–Pb dating of detrital zircons and zircon Hf and whole-rock Nd isotopic compositions for high-grade clastic metasedimentary rocks of the Slyudyansky Complex in eastern Siberia. This complex is located southwest of Lake Baikal and is part of an early Paleozoic metamorphic terrane in the eastern part of the Central Asian Orogenic Belt (CAOB). Our new zircon ages and Hf isotopic data as well as whole-rock Nd isotopic compositions provide important constraints on the time of deposition and provenance of early Paleozoic high-grade metasedimentary rocks as well as models of crustal growth in Central Asia. Ages of 0.49–0.90 Ga for detrital zircons from early Paleozoic high-grade clastic sediments indicate that deposition occurred in the late Neoproterozoic and early Paleozoic, between ca. 0.62–0.69 and 0.49–0.54 Ga. Hf isotopic data of 0.82–0.69 Ga zircons suggest Archean and Paleoproterozoic (ca. 2.7–2.8 and 2.2–2.3 Ga; Hfc = 2.5–3.9 Ga) sources that were affected by juvenile 0.69–0.82 Ga Neoproterozoic magmatism. An additional protolith was also identified. Its zircons yielded ages of 2.6–2.7 Ga, and showed high positive eHf(t) values of +4.1 to +8.0, and Hf model ages tHf(DM) = tHfc = 2.6–2.8 Ga, which is nearly identical to the crystallization ages. These isotopic characteristics suggest that the protolith was quite juvenile. The whole-rock Nd isotopic data indicate that at least part of the Slyudyansky Complex metasediments was derived from "non-Siberian" provenances. The crustal development in the eastern CAOB was characterized by reworking of the early Precambrian continental crust in the early Neoproterozoic and the late Neoproterozoic–early Paleozoic juvenile crust formation.
Keywords: Central Asian Orogenic Belt; Slyudyansky Complex; Zircon ages; Nd–Hf isotopes; Continental growth; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская